Gas-Liquid Contactors' Aeration Capacities When Agitated by Rushton Turbines of Various Diameters - Kracík, Tomáš; Moucha, Tomáš; Petříček, Radim (ACS omega, 2020)
Mass transfer processes are one of the most important operations in chemical, biochemical, and food industries worldwide. In the processes that are controlled by the gas-liquid mass transfer rate, the volumetric mass transfer coefficient k L a becomes a crucial quantity. The dataset was measured with the aim to create a correlation for k L a prediction in a non-coalescent batch under the wide range of experimental conditions. The dynamic pressure method, which was reported as physically correct in the past, was chosen to be the method for experimental determination of k L a. Our previous work targeted the k L a dependencies in viscous and coalescent batches resulting in correlations that are viable for the broad range of process conditions. We reported that the best-fit correlation is based on the hydrodynamic parameter circumferential velocity of impeller blades in the case of non-coalescent liquids in the vessel equipped by single or multiple impellers at a constant D/T ratio (diameter of the impeller to the inner diameter of the tank). Now, we focus on the influence of various impeller diameters on transport characteristics (mainly k L a) in a non-coalescent batch. The experiments are carried out in a multiple-impeller vessel equipped with Rushton turbines (of four diameters) and in both laboratory and pilot-plant scales. Various impeller frequencies and gas flow rates are used. We examine the suitability of the hydrodynamic description, which was reported in the past, to predict k L a also when the D/T ratio changes. We show that the correlation based on the energy dissipation rate better fits the experimental data and predicts k L a values more accurately in the case of varying D/T values. This correlation could be adopted in the design and scale-up of agitated devices operating with non-coalescent batches.